PENYELESAIAN SENGKETA NON-LITIGASI ANTARA KONSUMEN DAN JNE EXPRESS ATAS KESALAHAN PENGIRIMAN BARANG (STUDI KASUS PENGIRIMAN DI KOTA MALANG) - Nindia Rifdah Fakhirah; Kayla Mahiya Putri Wibowo; Elisabeth Hana Gracesoldy Sihombing; Desi Yayi Tarina (PT. Hasba Edukasi Mandiri, 2025)
One of the most common operational problems in the shipping service industry, including large companies such as JNE Express, is the misdelivery of goods. This study focuses on a case of a package being misdelivered from Malang to Banjarmasin due to incorrect labeling and data entry at the initial stage of the shipping process. The analysis shows that not only human error was the source of the problem, but also suboptimal internal control, inconsistent verification procedures at the branch level, and operational pressure caused by large shipping volumes. This study analyzes the management aspects and legal responsibilities of shipping service providers based on the Consumer Protection Law and the Commercial Code, which require companies to maintain the accuracy and security of goods during shipment.